SAT0025 Enhanced Capacity of MPO-ANCA Compared To PR3-ANCA for Inducing Neutrophil Extracellular Traps. (15th July 2016) - Kraaij, T.; Kamerling, S.; Bakker, J.; Pusey, C.; Scherer, H.U.; Toes, R.; Rabelink, T.; van Kooten, C.; Teng, O.
Abstract : Background: Neutrophil extracellular traps (NETs) are hypothesized to play an important role in the pathogenesis of ANCA associated vasculitis (AAV). On the one hand NETs can be part of the antigenic load in ANCA patients because NETs are covered with proteinase 3 (PR3) and myeloperoxidase (MPO) proteins (1). Presence of PR3 and MPO in a proinflammatory environment can induce ANCA autoantibody formation. On the other hand PR3- and MPO-ANCA autoantibodies by themselves have NET-inducing capabilities (1–3). The latter common pathway to induce NET release is intriguing taking into account the diverse clinical phenotype of granulomatosis with polyangiitis (GPA) versus microscopic polyangiitis (MPA). Objectives: The present study aimed to better characterize the NET-inducing capabilities of PR3-ANCA and MPO-ANCA by using a novel assay to quantify NET release. This assay uses highly sensitive, 3-dimensional confocal laser scanning microscopy (3D-CLSM) to quantify in vitro NET release upon incubation with PR3- and MPO-ANCA. Methods: Sera from 62 PR3+ patients, 36 MPO+ patients and 14 healthy subjects were collected. To induce and quantify NET release, healthy PKH-labelled neutrophils were seeded in a 96-well plate and stimulated with 10% sera. After 3¾ hours, cells were incubated with Sytox green for 15 minutes to stain NETs. NET release was imaged by automated 3D-CLSM and quantified with digital image analysis. NET release was represented as NET area corrected for neutrophil count. NET release was correlated with PR3- and MPO-ANCA titers as well as with clinical disease characteristics. Results: Both MPO-ANCA and PR3-ANCA sera induced significant NET release (mean ± SEM for MPO-ANCA 4.29 ± 0.60, p<0.0001 and 1.56 ± 0.20 for PR3-ANCA, p<0.01) as compared to NHS (0.17 ± 0.04). Moreover, MPO-ANCA induced significantly higher NET release than PR3-ANCA (p<0.0001) (Figure 1 ). NET release did not correlate with either MPO-ANCA titers (r=0.17, p=0.35) or PR3-ANCA titers (r=-0.04, p=0.79). We, then, categorized according to ANCA serotype and NET release. Conclusions: We here demonstrate that MPO-ANCA has significantly enhanced NET-inducing capabilities compared to PR3-ANCA, which is independent of ANCA serum titers. These data point to a direct pathogenic role of ANCA autoantibodies in the perpetuation or relapse of AAV disease. Future studies will need to investigate whether ANCA-induced NET release can be a functional test to identify pathogenic from non-pathogenic ANCA in AAV patients. References: Kessenbrock, K., M. Krumbholz, U. Schönermarck, W. Back, W. L. Gross, Z. Werb, H.-J. Gröne, V. Brinkmann, and D. E. Jenne. 2009. Netting neutrophils in autoimmune small-vessel vasculitis. Nat. Med. 15: 623–625. Nakazawa, D., H. Shida, U. Tomaru, M. Yoshida, S. Nishio, T. Atsumi, and A. Ishizu. 2014. Enhanced Formation and Disordered Regulation of NETs in Myeloperoxidase-ANCA-Associated Microscopic Polyangiitis. J. Am. Soc. Nephrol. 1–8. Ma, Y.-H., T.-T. Ma, C. Wang, H. Wang, D.-Y. Chang, M. Chen, and M.-H. Zhao. 2016. High-mobility group box 1 potentiates antineutrophil cytoplasmic antibody-inducing neutrophil extracellular traps formation. Arthritis Res. Ther. 18: 2. Disclosure of Interest: None declared